Ultrafast high energy electron lens radiography suitable for transient electromagnetic field diagnosis. (25th January 2022) - Xiao, J.H.; Du, Y.C.; Li, H.Q.; Zhao, Y.T.; Sheng, L.
Abstract: Transient electromagnetic fields — during or after laser/particle beam-target interaction — are a significant and hardly explored parameter. This paper proposes a new method for measuring transient electromagnetic fields, based on ultrafast high-energy electron lens radiography, that has a high tolerance for matter in the diagnosed region. With this method, a continuous point strength diagnosis helps to obtain delicate. Furthermore, dual-band diagnosis can be used to determine the field direction. To verify its feasibility, a 50 MeV electron lens radiography beamline was designed and optimized and a preliminary simulation for diagnosing circular magnetic fields ranging from 170 T·μm to 680 T·μm was performed. For a number density of 2000/pixel and ±10% non-uniformity, ±15% diagnostic field strength accuracy has been obtained. The direction diagnosis also works well. Combined with the advantages of high-energy electron beams, ultrafast high-energy electron lens radiography is suitable for transient electromagnetic field diagnosis.